Paracoccin Induces M1 Polarization of Macrophages via Interaction with TLR4 - Freitas, Mateus S.; Oliveira, Aline F.; da Silva, Thiago A.; Fernandes, Fabrício F.; Gonçales, Relber A.; Almeida, Fausto; Roque-Barreira, Maria C. (Frontiers in Microbiology, 2016)
The fungal human pathogen Paracoccidioides brasiliensis contains paracoccin (PCN), a multi-domain protein that has lectin and N-acetyl-glucosaminidase activities, which account for its effects on the growth and morphogenesis of the fungus and on the activation of host macrophages through its interaction with TLR N-glycans. With the purpose of detailing the knowledge on the effects of PCN on macrophages, we used recombinant PCN expressed in Pichia pastoris (p-rPCN) to stimulate isolated murine peritoneal macrophages. The activation of these cells manifested through the release of high levels of inflammatory mediators, such as nitric oxide, TNF-α, IL-12p40, and IL-6. Furthermore, peritoneal macrophages stimulated with p-rPCN increased the relative expression of STAT1, SOCS3, and iNOS2 mRNA (M1 polarization markers). However, the expression of Arginase-1, Ym-1, and FIZZ1 (M2 polarization markers) remained at basal levels. Interestingly, the observed M1 macrophages’ polarization triggered by p-rPCN was abolished in cells obtained from knockout Toll-like receptor-4 mice. In this case, the p-rPCN-induced production of pro-inflammatory mediators was blocked too. These results demonstrate that the classical activation of macrophages induced by paracoccin depends on TLR4. Taken together, the results of our study indicate that paracoccin acts as a TLR agonist able to modulate immunity and exerts biological activities that favor its applicability as an immunotherapeutic agent to combat systemic fungal infections.